The ontogeny of the postcranial skeleton in saddle-back tamarins, Leontocebus fuscicollis and callimicos, Callimico goeldii (Callitrichidae, Primates) - Urbani, Bernardo (Anthropological Review, 2023)
Ontogenetic studies of callitrichid anatomy are limited to research focused mainly on postcranial skeleton of adults. The goal of this study is to compare the ontogeny of postcranial skeletal development in Goeldi’s monkeys (i.e., callimico; Callimico goeldii) with the corresponding data on saddle-back tamarins (Leontocebus fuscicollis). The intermembral, humerofemoral, brachial, crural, and ulna-radius indices of callimicos and saddle-back tamarins were calculated and compared among different age classes in order to assess the implications for their ecology and behavior. Ontogenetic trajectories, including age at growth cessation, were also calculated. It is shown that for a given hindlimb length, L. fuscicollis has longer forelimbs compared to C. goeldii, maintaining this proportion across all age classes. A relatively elongated forelimb observed in L. fuscicollis may have a mechanical role in reducing the force of impact when landing on large vertical substrates. In contrast, hindlimb length and pattern of hindlimb development (such as derived features of the ankle that enhance stability) in callimicos appear to play a critical role in propulsion during trunk-to-trunk leaping. These differences may affect niche partitioning, foraging strategies, and substrate use.